Accuracy of Nearly Extinct Cohort Methods for Estimating Very Elderly Subnational Populations. (1st July 2015) - Terblanche, Wilma; Wilson, Tom
Abstract : Increasing very elderly populations (ages 85+) have potentially major implications for the cost of income support, aged care, and healthcare. The availability of accurate estimates for this population age group, not only at a national level but also at a state or regional scale, is vital for policy development, budgeting, and planning for services. At the highest ages census-based population estimates are well known to be problematic and previous studies have demonstrated that more accurate estimates can be obtained indirectly from death data. This paper assesses indirect estimation methods for estimating state-level very elderly populations from death counts. A method for incorporating internal migration is also proposed. The results confirm that the accuracy of official estimates deteriorates rapidly with increasing age from 95 and that the survivor ratio method can be successfully applied at subnational level and internal migration is minor. It is shown that the simpler alternative of applying the survivor ratio method at a national level and apportioning the estimates between the states produces very accurate estimates for most states and years. This is the recommended method. While the methods are applied at a state level in Australia, the principles are generic and are applicable to other subnational geographies.